Metabolic reprogramming by ex vivo glutamine inhibition endows CAR-T cells with less-differentiated phenotype and persistent antitumor activity. (10th July 2022) - Shen, Luyan; Xiao, Yefei; Zhang, Chaoting; Li, Shance; Teng, Xia; Cui, Likun; Liu, Ting; Wu, Nan; Lu, Zheming
Abstract: The inadequate in vivo persistence of chimeric antigen receptor (CAR)-modified T cells has been shown to lead to poor therapeutic efficacy and disease recurrence. In vivo persistence is associated with the differentiation subsets infused, with less differentiated TN or TCM conferring superior renewal capacity and antitumor immunity compared to TEM or TEFF . However, ex vivo expanded CAR-T cells exhibit phenotypic heterogeneity with majority of TEM or TEFF subsets and very low populations of TN and TCM . The transition of differentiation subsets is closely correlated with T cell metabolism fitness. Effector T cell differentiation from TN or TCM requires glutamine uptake and metabolism. Using a CD19-specific CAR, we demonstrated that glutamine inhibition by adding the glutamine antagonist 6-Diazo-5-oxo-l -norleucine (DON) into the culture endows CAR-T cells with enhanced mitochondrial OXPHOS utilizing fatty acids and reduced glycolytic activity, and retains more TN or TCM subsets. DON- pretreated CAR-T cells exhibited stronger cytotoxic lysis in vitro and more robust elimination of tumor burdens in vivo . This study suggests that glutamine inhibition ex vivo would be a potential approach for modulating metabolism and differentiation state to improve the efficacy of CAR-T cell therapy. Highlights: Glutamine inhibition retained TN and TCM subsets in CAR-T cells. Glutamine inhibition induced metabolic reprogramming adapted to TN and TCM subsets. Glutamine inhibition induced transcriptional programs consistent with a memory-like phenotype. Glutamine inhibition endowed CAR-T cells with superior anti-tumor activity.